Students’ Word-Problem Errors Identified Through Newman’s Procedure in a Problem-Based Learning Classroom - Anggraini, Heni; Surya, Ed (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Low mathematics achievement, particularly in solving word problems, remains a persistent challenge for students. This study aims to analyze (1) whether students’ errors in solving word problems through the Problem-Based Learning (PBL) model are lower than those in conventional learning, (2) whether students’ mastery learning in the PBL model is higher than that in conventional learning, and (3) how well students are able to solve mathematical word problems based on Newman’s procedure when taught using the PBL model. A mixed methods approach was employed, combining a quasi-experimental design with a qualitative descriptive method. Data were collected through written tests for the quantitative component and in-depth interviews for the qualitative component. The quantitative data were analyzed using an Independent Sample t-test. The findings indicate that students taught with the PBL model experienced a notable reduction in errors across all stages of Newman’s procedure. These results demonstrate that the PBL model effectively minimizes student errors, increases mastery learning, and strengthens students’ ability to solve mathematical word problems. Overall, the study recommends the use of the PBL model in mathematics classrooms to foster deeper understanding and enhance the relevance of learning to students’ everyday experiences.